Interfaith marriage in Indonesia: A normative analysis of legal arrangements and judicial practices - Yenny Febrianty; Putri Ayi Winarsasi; Lilis Suryani; Vivi Hayati; Sahrul Sahrul (Priviet Social Sciences Journal, 2026)
Interfaith marriage in Indonesia persists in inciting legal controversies due to disparate interpretations and implementations of regulations by the court. This article aims to analyze the legal framework regulating interfaith marriage in the Indonesian legal system, emphasizing statutory provisions and judicial decisions, while evaluating how discrepancies in the interpretation and application of these laws affect legal certainty and the protection of citizens' constitutional rights. This study utilizes normative juridical methodologies, incorporating legislative, conceptual, and case approaches, to analyze Law Number 1 of 1974 on Marriage, Law Number 23 of 2006 on Population Administration, Constitutional Court Decisions Number 68/PUU-XII/2014 and Number 24/PUU-XX/2022, as well as various district court rulings regarding the registration of interfaith marriages. The study's results reveal that, under Indonesian law, the validity of marriage is largely regulated by religious law, but the state retains authority over administrative issues to provide legal order and clarity. Prior to the implementation of rigorous judicial standards, the court used diverse interpretations, resulting in discrepancies in decisions and legal uncertainty. This conflict stems not from an absence of standards but from inconsistencies in legal enforcement. The Constitutional Court has affirmed that restrictions on interfaith marriage do not violate constitutional rights when based on religious beliefs and Article 28j of the 1945 Constitution of the Republic of Indonesia. The issuance of Supreme Court Circular Letter Number 2 of 2023 has improved normative legal clarity; nonetheless, the subsequent obstacle lies in the consistency of its application in judicial practice.